Penerapan Pendidikan Islam tentang Akhlakul Karimah pada Masa Pandemi Covid-19 - Salsabila, Unik Hanifah; Aliyah, Andi Dzakiyatul; Rizkilla, Indah Purwanda Hafizh Ananda; Adli, Al a’Raaf Wira (Lembaga Yasin AlSys, 2022)
An ideal and purpose of education in addition to educating the public is also to form characters with good morals and behavior, because in Islam and the proverb says that adab is higher than science which means that before studying science we must first study morality, at the time of this is a very rare matter of morality or in other languages, namely the moral crisis that is happening at this time, this is not only happening among school children but in the community. Moreover, at this time we are being haunted by the Covid-19 outbreak which causes all activities to be hampered and now it is done online so that the cultivation of character or moral values becomes more difficult, becoming a problem that cannot be taken lightly because character will determine the quality of society. Republic of Indonesia, therefore we are conducting research to find ways to deal with the problem of the moral crisis or lack of moral education during the Covid-19 pandemic.